The Effect of Financial Variables, CSR Management, And Company Size on Tax Aggressivity - Muhammad Ridwan Yusuf; Yuli Chomsatu Samrotun; Anita Wijayanti (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
This study describes how the influence caused by research variables such as profitability, inventory intensity, capital intensity, leverage, corporate social responsibility (CSR), audit committee size, company size, corporate governance, on tax aggressiveness. In this study, data will be taken from mining and industrial companies listed on the Indonesian Stock Exchange (IDX) within 3 years, starting from 2017 - 2019. The research test used in this study is multiple linear regression analysis, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. This study showed that the results of capital intensity and leverage affect tax aggressiveness, while profitability, inventory intensity, CSR, audit committee, company size, corporate governance do not affect tax aggressiveness.